Rotinas organizacionais e a influência dos antecedentes internos e externos na variedade sequencial - Spuldaro, Juliano Danilo (2016)
Which factors influence the variety of task sequences of organizational routines? This study is focused on analyzing how antecedents influence sequential variety of organizational routines. Routines provide efficiency and coordination to organizational processes through standardization and specialization of tasks and their threads. Organizational routines literature postulates that high levels of variability may be important to maintain flexibility in organizational processes (Feldman and Pentland, 2003). Sequential variety is considered the most reliable expression of diversity in sequences of tasks configurations in an organizational routine. This study proposes a qualitative method of analysis of the sources of sequential variety. The framework of reference was proposed by Becker (2005b) and includes the antecedents task complexity, task interdependence, time pressure, uncertainty pertaining to the task and turnover of agents as well as characteristics and results of organizational routines. To achieve this goal two observations were performed in emergency rooms of health organizations chosen due to their performance. The organizational routine of care in emergency rooms is an important process to be studied because it is the main way of access to treatments in the two hospitals analyzed. Furthermore, the routine enhances efficiency and is characterized by meet international quality standards. The data were organized by a content analysis adapted to the study of sequential variety of organizational routines. Thanks to this analysis it was possible to analyze the sources sequential variety and discuss them in the context of the literature of organizational routines. Four main sources of sequential variety were identified: priority setting which is related to the time pressure; need for expertise linked to complexity of the task; increment of information for diagnosis and treatment that is related to the uncertainty of the task; and lasting of treatment linked to uncertainty and interdependence of the task. There is no evidence that turnover of agents influences the sequential variety. This study suggests that the antecedents identified as influential in the sequential variety could be seen as two groups. The external antecedents arising from issues related to the multiplicity of conditions of patients are time pressure and task uncertainty. Internal records are more attached to rules and organizational resources and include the complexity and interdependence of the task.